The style of EU directives and the discourse of expert rationality - Molek-Kozakowska, Katarzyna (Stylistyka, 2019)
This article is devoted to the notion of expert rationality, understood as one of the central epistemic regimes of the discourse of the European Union. Expert rationality is instrumenlal to the legitimization of EU directivity and control of centrally designed political, economic, and sociál Solutions for an integrating Europę. From a philological perspective, however, it is worth investigaling how expert rationality tends to be textually realized. Therefore, this article discusses the stylistic properties of the genre of the directive based on Directive 98/79/EC of 27 October 27 1998 on in vitro diagnostic medical devices. The analysis focuses on the identification of such stylistic resources and the strategie applications that underpin the ideology of expert rationality.